Mudança organizacional na UFPA: institucionalização da participação dos técnico-administrativos no processo eleitoral para dirigentes das unidades acadêmico-administrativas - CONCEIÇÃO, Juliano Cássio da Silva (Universidade Federal do Pará, 2019)
Nowadays, the organizations live in an increasingly, dynamic and changing environment. These changes are in the light of technological advances, economic, political, social contexts, etc. This requires more and more arrangement develop the capacity to adapt new conditions. This work is therefore the possibility of organizational change within the Federal University of Pará, with regard to the institutionalization of the participation of technical administrative in the election process for the positions of academic managers of the administrative units.Thus, this research aims to identify whether there is resistance to this reform and what it is possible causes, as pressure from both the internal and external environment, converge in favor of management reorganize. The chosen setting for the research was the University Council - CONSUN. It is the collective space of deliberation and where decisions are made related to the implementation of an organizational change of this nature. It was made an exploratory and descriptive research, the objective point of view, and from a technical, biographic and documentary. The quantitative method was used, which primary data were obtained from the application of questionnaires between the three categories of counselors: professors, learners and technicians in order to acquire the understanding of them about the subject, they were divided in two groups (Professor and no Professor). The analysis was done by statistical techniques, it concluded that CONSUN is a decision making environment with a high degree of receptivity to organizational changes. The investigate also allowed to identify the main causes of resistance perceived by both groups inside the council. In the way in which the organizational change that is the purpose of this study, the comparative tests make possible to notice significant differences in perception of the two groups, from a specified time that the professor group demonstrated resistance to organizational change